2018
DOI: 10.3390/app8071060
|View full text |Cite
|
Sign up to set email alerts
|

Study on Cleaning the Surface of Stainless Steel 316 Using Plasma Electrolysis Technology

Abstract: Featured Application: The proposed method may benefit the cleaning process of the metals that undergo surface treatment. Especially, this method can be used to fabricate microstructures on the surface of the stainless steel to enhance the self-cleaning and corrosion resistance properties.Abstract: This research utilizes a plasma electrolysis technique to clean the surface of stainless steel 316. The resulting microstructure enhances the self-cleaning properties of the stainless steel surface. The position of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Lin et al reported "Study on Cleaning the Surface of Stainless Steel 316 Using Plasma Electrolysis Technology" [8]. This research utilized a plasma electrolysis technique to clean the surface of stainless steel 316.…”
Section: The Topics Of Applied System Innovationmentioning
confidence: 99%
“…Lin et al reported "Study on Cleaning the Surface of Stainless Steel 316 Using Plasma Electrolysis Technology" [8]. This research utilized a plasma electrolysis technique to clean the surface of stainless steel 316.…”
Section: The Topics Of Applied System Innovationmentioning
confidence: 99%
“…The collected feedback from anonymous users also showed that the EPMRS sufficiently reflect their preference on music. Lin et al reported "Study on Cleaning the Surface of Stainless Steel 316 Using Plasma Electrolysis Technology" [8]. This research utilized a plasma electrolysis technique to clean the surface of stainless steel 316.…”
Section: The Topics Of Applied System Innovationmentioning
confidence: 99%
“…Chen et al compared the methods for gaining EMI SE and subsequently composed a complete shielding network with improved EMI SE [16]. The comfort of conductive fabrics compromises when the constituent metallic wires could not be enwrapped completely [17]. As a result, the conductive fabrics demonstrate oxidation corrosion, which decreases the shielding effectiveness against electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%